2021
DOI: 10.21203/rs.3.rs-692874/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stock-Outs of Essential Medicines Among Community Health Workers (CHWs) In Low- And Middle-Income Countries (LMICs): A Systematic Literature Review of The Extent, Reasons, And Consequences

Abstract: Background: This paper explores the extent of community-level stock-out of essential medicines among Community Health Workers (CHWs) in Low- and Middle-Income Countries (LMICs) and identifies the reasons for and consequences of essential medicine stock-outs. Methods: A systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was conducted. Five electronic databases were searched with a prespecified strategy and the grey literature examined, January 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…While this study did not look specifically at equity, previous studies have established that many community-oriented primary health care programs have an explicit equity promotion component, 28 CHWs promote equitable access to promotive, preventive, and curative services at the household level, 29 and CHW-delivered interventions (including home visits) improve equity in maternal and newborn health. 30 Despite such high potential and powerful equity dividend, the majority of CHWs globally remain unpaid, without essential medications, 31 inadequately supervised, and largely unsupported. This evidence suggests that the opportunity cost of not professionalizing CHWs may be substantially larger than previously estimated in light of the inevitability of future pandemics.…”
Section: Chws Maintain Essential Health Services During Pandemicsmentioning
confidence: 99%
“…While this study did not look specifically at equity, previous studies have established that many community-oriented primary health care programs have an explicit equity promotion component, 28 CHWs promote equitable access to promotive, preventive, and curative services at the household level, 29 and CHW-delivered interventions (including home visits) improve equity in maternal and newborn health. 30 Despite such high potential and powerful equity dividend, the majority of CHWs globally remain unpaid, without essential medications, 31 inadequately supervised, and largely unsupported. This evidence suggests that the opportunity cost of not professionalizing CHWs may be substantially larger than previously estimated in light of the inevitability of future pandemics.…”
Section: Chws Maintain Essential Health Services During Pandemicsmentioning
confidence: 99%
“…Compared to 2014, this has improved as there was unstructured approach with no de ned rules or processes to drive resupply as indicated in a study done from Ethiopia, Malawi, and Rwanda. In this research, ndings revealed that 62% of CHWs resupplied based on (nonstandard) documentation; 19% of CHWs used a variety of ("other") methods; 8% of CHWs provided the same as previous month before the study; 7% and 4% of CHWs "didn't know" or used a formula, respectively [19].…”
Section: Discussionmentioning
confidence: 75%
“…Products were considered available if product is not stock-out (if physical count is not zero) on the day of visit in the CHWs store. [19] This study reported 3.2% antimalarial stock out on the day of the visit. Compared to other African countries, Rwandan prevalence of antimalarial stock out is a bit lower as indicated by a study conducted in Uganda, which stated that ACTs/Coartem -20/120 mg, a drug used to treat Malaria, was the least available (at 3.3 %) of all the iCCM (Integrated Community Case Management) medicines [12].…”
Section: Discussionmentioning
confidence: 87%
“…Fourth, our analysis did not account for the possibility of accessing health services across national boundaries, an important consideration for border communities and migrant populations. Fifth, our analysis did not account for social and economic barriers to care-seeking which may impact access to and use of health services independently of physical accessibility or through interactions with physical accessibility [60][61][62]. Lastly, our analysis did not consider the stockouts of equipment, supplies or commodities, quality of services and the potential for bypassing [63,64].…”
Section: Limitationsmentioning
confidence: 99%